Restauração florestal visando à conservação de recursos hídricos por meio da combinação linear ponderada - Sartori, Anderson Antonio da Conceição [UNESP]; Nossack, Fábio Ávila [UNESP]; da Silva, Ramon Felipe Bicudo [UNESP]; Zimback, Célia Regina Lopes [UNESP] (My University, 2012)
This study evaluated using of Multicriteria Evaluation in a GIS, specifically by Weighted Linear Combination Method for generation of map of priority areas for forest restoration in the initial part of River Pardo Basin, SP, in order to water resources conservation. Aiming to define criteria and restrictions it was used Participatory Techniques, and the following factors had been selected: proximity of the hydrographic network, proximity of forest cover, slope and erodibility of soil. To calculate the weight to each factor it was used the decision-making process, known as Analytic Hierarchy Analysis, this method consists of a paired comparison of factors to determine the relative importance of each. According to Weighted Linear Combination, the very high priority areas have a more limited spatial distribution, with an apparent concentration around the water bodies, outlining a buffer to the river system. The proximity factor of the hydrographic network, and enables the connection forestry, contributed, along with the factor of proximity to forest cover, so there would be the definition of most of the areas with the highest priority in the basin, which concentrate the largest areas of forest and native riparian areas along the hydrographic.
Forest restoration aiming at the conservation of water resources by Weighted Linear Combination
Keywords: GIS; Multicriteria evaluation; Priority areas